Letter (copy) - Comite De Unificacion ; Unión General de Trabajadores de España ; Confederación Nacional del Trabajo (Spain); Tewson, Vincent
010-0111-001 HVT/EK/465. Secretary's. 2nd September, 1936. Comite De Unificacion, U.G.T. C.N.T., Alcira, Spain. Dear Comrades, We have your letter of the 19th August and feel that the best thing we can do to help is to forward your letter to the Co-operative Wholesale Society in this country. With our sincere good wishes for the success of the loyal forces, I am, Yours sincerely, Assistant Secretary. 292/946/10/120